INTERPRETASI DATA ANOMALI MAGNETIK UNTUK MENENTUKAN HEAT SOURCE DARI SUMBER PROSPEK PANAS BUMI DI DAERAH CISOLOK - CISUKARAME, SUKABUMI - ARUM KHOERUNNISA, - (2021)
One evidence of geothermal manifestations in the form of geyser found in the Cisolok area, Wangunasari village, Sukabumi district. Geyser the proof of magma activity that occurs beneath the surface around the manifestation. Therefore, knowledge about below surface manifestation is necessary to find out the geothermal system in the form of a heat source. This research uses geophysical methods in the form of geomagnetic. The aim of this research is for take a look at the distribution of magnetic anomalies in the area around the manifestation and to identify the below surface that reflecting the geothermal layer in the form of a heat source by doing forward modeling of magnetic data. Magnetic anomaly distribution data obtained from 45 measurement points. The data processing stage begins with performing diurnal correction, IGRF correction (International Geomagnetic Reference Field), reduce anomalies using the RTP process, separation of anomalies using the Upward Continuation process 3 times with the values ​​used are 50,100, and 150m. Meanwhile, modelling was finished by using magnetic anomaly value that have been separated. The distribution of magnetic anomalies obtained has a range of low anomaly values ​​at -69.3 nT and high anomalies at 287.3 nT. The distribution of magnetic anomalies that have been reduced by RTP process has a range of low anomaly values ​​ranging from -189.8 nT to high anomalies of 414 nT. The result of 2D modeling shows that there is a rock layer which is indicated as a heat source which is shown by the modeling of slices 1 and 2 at a depth of 170m which is in the south direction of the research path. The rock is an andesite igneous rock with a susceptibility value of 0.016051 cgs. This research is expected to be able to provide information to be used as a reference for further research and it is hoped that the development of a geothermal power plant (PLTPb) is expected. Kata kunci : Geomagnetic methods , Geothermal , Heat source , Reduce To Pole, Upward Continuation, 2D of modelling .